Journalist's relationship with political authority in Egypt 1960-2011 - Goda, Heba Ahmed Awad; Abdi Al- Maged Ibrahim, Laila (International Journal of Communication and Society, 2022)
The study of the journalist's relation with political authority in Egypt from 1960 to 2011 seeks to reveal, describe, analyze and interpret the journalist's relation with political authority in Egypt during this period and to reach a model that explains the factors affecting the journalist's relation with political authority. This is by exposing the political, legislative, social and cultural factors affecting the journalist's relationship with political authority during the period of study.  This paper aims to reveal the personal characteristics of successive political leaders during the period of study, and their role in shaping the relationship between the journalist and the political authority in Egypt.  In addition to revealing the social development, personal characteristics and professional gradations of a sample of prominent journalists during the course of the study, and the role these factors played in shaping the relationship between the journalist and the political authority in Egypt.  The study found that the media in general, and the press in particular, play a role in political life, whether by expressing interest groups and opinion leaders, or by relying political systems on them to reach out to the public and promote their policies at home and abroad alike.  Media has also proved to be the link between the public on the one hand and political decision makers on the other. The results also confirmed that the media helps the political systems to create public opinion in favor of their policies or to mobilize public opinion against those opposing their policies, which in both cases is a dangerous and vital role.  The study also revealed that the mass media can influence the minds and emotions of the public and change their attitudes and behavior in a way that serves their policies and achieves the interests and goals of the political authority.  The results of the study also confirmed that the legislation and laws prevailing in each country determine the form of the relationship between the press and the political authority.  The results of the study also showed that the forms of relations between journalists and politicians vary, sometimes they are confused, and sometimes stable